Analisis Kemampuan Rasio Keuangan Dalam Memprediksi Pertumbuhan Laba Pada Perusahaan Otomotif Yang Terdaftar Di Bursa Efek Indonesia Periode 2005-2007 - Sri Handayani . (Jurnal Manajemen Maranatha, 2010)
This research is aimed to empirically study the effect of financial ratios-liquidity ratio, leverage, activity ratio, and profitability ratio- on profit growth of the automotive firms registered between 2005-2007 on Indonesia Stock Exchange (IDX). The data is sampled using purposive sample method and analized by multiple regression to answer the hyphotesis. The result that all the variables (Current ratio, Gross Profit Margin, Inventory Turnover and Debt to Assets) have significantly affect to profit growth with level of significance 5 percent. So we concluded the independent variables can predict profit growth for one year later.Keywords: Current Ratio, Gross Profit Margin, Inventory Turnover dan Debt to Asset, profit growth